Nurturing the sustainable food systems: crafting policies and practices for crop diversification in Bangladesh - Nandi, Ravi; Krupnik, Timothy J.; Kabir, Wais; Jackson, Tamara (Frontiers in Sustainable Food Systems, 2024)
Bangladesh's agriculture, dominated by rice, faces sustainability risks, necessitating a focus on crop diversification (CD). This study explores the policy environment and project implementation promoting CD from 1971 to present, using an analytical framework by the CGIAR-International Maize and Wheat Improvement Centre (CIMMYT). Despite numerous initiatives, progress is stifled by historical biases and coordination gaps among government agencies, affecting project effectiveness. Findings indicate that most efforts are project-driven and transient, lacking integration into national budgets which could ensure sustainability. This study suggests enhancing market linkages and integrating CD into annual budgets to address funding and market development challenges, offering actionable guidelines to bolster long-term agricultural resilience in Bangladesh.